Online equation for latex application - Toh, Peck Yean (2017)
In the universities, Latex is one of the tool for producing Mathematical Expression in order to prepare scientific documents. Latex requires programming language to produce Mathematical Expression. I order to produce Mathematical Expressions (ME), it is also possible to write ME on electronic device and convert the handwritten ME to Latex. This requires techniques to recognise the handwritten ME. There are many possible techniques to recognise the handwriting mathematical expression such as Optical Character Recognition(OCR). The OCR is the most popular technology tool to read the handwriting text. However, the structure of the input data of electronic device is basically a set of strokes with a sequence order of X and Y coordinates. Hence, this project is related to the study of recognising the handwritten mathematical expression in Android mobile application. By adapting the Online Handwriting Recognition technique, the data values of handwritten ME will be processed, segmented and recognised through several techniques in order to convert the handwritten ME to typeset ME. This project also involves using the Support Vector Machine as the classification for mathematical symbol recognition. The performance evaluation of the Support Vector Machine has been carried out in this project. The conclusion and the future work have also been described in the last chapter of this dissertation.